The politics of participative management in South Africa: a case study of PG Bison Limited, 1986 to 1996 - Evans, Gavin (My University, 1997)
While employee participation has existed in various forms since the late 19th century, the thinking behind terms like 'participative management' and 'stakeholding' began to take root after the second world war in some companies in the major industrial nations ...[No abstract provided. Information taken from first chapter]
A thesis submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements of the degree of Doctor of Philosophy, 1997
Keywords: Management--Employee participation--South Africa